2018
DOI: 10.4103/jnsbm.jnsbm_108_17
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality of prescription writing among dental and medical students and practitioners in Kerala

Abstract: Background:The medical prescription is a valid and legal document. Prescriptions can also be used as a measure of the quality of medical education, observance of the laws and regulations, and sociocultural beliefs.Aims:To assess the quality of prescription written by dental and medical students and practitioners.Settings and Design:A cross-sectional study was conducted in three dental and two medical colleges in Kerala covering 345 participants (dental - 235 and medical - 110).Materials and Methods:Simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 19 publications
(23 reference statements)
1
20
0
1
Order By: Relevance
“…The effect of training on the reduction of prescription errors was shown among dentistry students (14,15), medical students (10,16) and general practitioners (17,18). Prescription opportunities for midwifery students are less 4…”
Section: Discussionmentioning
confidence: 99%
“…The effect of training on the reduction of prescription errors was shown among dentistry students (14,15), medical students (10,16) and general practitioners (17,18). Prescription opportunities for midwifery students are less 4…”
Section: Discussionmentioning
confidence: 99%
“…Indication of patient's name and the date of the prescription are of vital importance of prevent misappropriation and loss. 6,14 Despite the fact that the skills of almost half of the students in writing out the drug orders on the prescriptions was deemed high, none of the students completely observed the principles for recording the drug orders. In a similar study, Guzmán-Álvarez et al evaluated a total of 66 lastyear dental students at Universidad Nacional Autónoma de México and reported that only 20 students (30.3%) followed the WHO Guide to Good Prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…Signing a prescription is necessary for its formality and validity and is legally valuable: a prescription without a signature cannot be filled. 6 It appears that medical and dental students do not receive proper education in writing correct and complete prescriptions during their studies. The current educational programs are mainly based on basic principles of pharmacology, classification of drugs, side effects and toxicosis by drugs, with less time and attention devoted to the clinical administration of drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of medical education can be measured by prescriptions. 1,2 Prescription writing reflects the competency of the physician. 3 The recent medical graduates are practicing future physicians and also they are the stakeholders.…”
Section: Introductionmentioning
confidence: 99%